2013
DOI: 10.1089/vbz.2012.1242
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Equine Encephalitis Virus: High Seroprevalence in Horses from Southern Quebec, Canada, 2012

Abstract: Eastern equine encephalitis virus (EEEV) is a highly pathogenic arbovirus that infects humans, horses, and other animals. There has been a significant increase in EEEV activity in southeastern Canada since 2008. Few data are available regarding nonlethal EEEV infections in mammals, and consequently the distribution and pathogenicity spectrum of EEEV infections in these hosts is poorly understood. This cross-sectional study focuses on the evaluation of viral activity in southern Quebec's horses by seroprevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…However, the seroprevalence of antibodies to WNV in humans in this study was relatively comparable with the results from a serosurvey conducted in southern Ontario after the 2002 WNV outbreak in humans (3•1% [38]) and helps support the notion that humans are rarely bitten by WNV-infected mosquitoes in eastern Canada. Moreover, as discussed in Rocheleau et al [4], there are specific limitations to the use of serology in horses pertaining to the fact that clear information on vaccination status must be obtained in each horse for adequately interpreting WNV and EEEV serological results. However, to our knowledge, current vaccination protocols have no impact on serological status for CSGV since no vaccines are currently available for these mosquito-borne bunyaviruses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the seroprevalence of antibodies to WNV in humans in this study was relatively comparable with the results from a serosurvey conducted in southern Ontario after the 2002 WNV outbreak in humans (3•1% [38]) and helps support the notion that humans are rarely bitten by WNV-infected mosquitoes in eastern Canada. Moreover, as discussed in Rocheleau et al [4], there are specific limitations to the use of serology in horses pertaining to the fact that clear information on vaccination status must be obtained in each horse for adequately interpreting WNV and EEEV serological results. However, to our knowledge, current vaccination protocols have no impact on serological status for CSGV since no vaccines are currently available for these mosquito-borne bunyaviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples from horses >18 months of age were collected in 2012 as described previously [4]. All horses resided within Montérégie, Lanaudière or Laurentides regions ( Fig.…”
Section: Horsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The serosurvey dataset included 190 horses sampled in 2012 from 92 barns located within the study area. These horses had never been vaccinated against EEEV at the time of sampling, and 15 were seropositive to EEEV [7]. In addition to EEEV serological results, this dataset included information on horse characteristics (age, sex, breed), animal management (use of mosquito repellent, time spent outside daily, use of horse protective fly sheets or blankets), and characteristics of the barn in which they were housed (type of housing, use of window and door screens).…”
Section: Datasetsmentioning
confidence: 99%
“…In 2012, an equine EEEV serosurvey conducted in the same region revealed that more than 6% of horses had been infected with EEEV, which suggests that ecological niches (i.e. appropriate habitat, vectors and virus) exist to sustain EEEV transmission including potential spillover to human populations [7]. The characteristics of these ecological niches have, however, never been precisely identified.…”
Section: Introductionmentioning
confidence: 99%